Keefektifan Komunikasi Antarpribadi di Lingkungan Dinas Komunikasi Dan Informatika Jawa Barat - Gatra Fairuz Khalda; Agus Setiaman; Detta Rahmawan (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
This research aims to gain a deeper understanding of the Effectiveness of Interpersonal Communication in the West Java Communication and Information Office environment, specifically how the government agency communicates with the public and its impacts on various aspects. The research method employed is a Descriptive Quantitative approach. The total number of respondents in this study is 80 permanent employees of the West Java Communication and Information Office. Data collection was conducted by distributing questionnaires to all sampled employees of the West Java Communication and Information Office. The results of the research indicate that the Effectiveness of Interpersonal Communication in the West Java Communication and Information Office environment falls into the high category. This is evidenced by the high values assigned by the respondents to the five dimensions of Interpersonal Communication Effectiveness. Thus, it can be concluded that the Effectiveness of Interpersonal Communication among the employees of the West Java Communication and Information Office is considered effective.